Response profiles of BV2 microglia to IFN-γ and LPS co-stimulation and priming - Pan, Meng Liy; Ahmad Puzi, Nur Nabilah; Ooi, Yin Yin; Ramasamy, Rajesh; Vidyadaran, Sharmili (Multidisciplinary Digital Publishing Institute, 2023)
(1) Background: The latest research illustrates that microglia phenotype is not the binary ‘resting’ and ‘activated’ profiles. Instead, there is wide diversity in microglia states. Similarly, when testing different stimulation protocols for BV2 microglia, we discovered differences in the response of the cells in terms of the production of intracellular ROS (iROS), nitric oxide (NO), CD40 expression, and migratory capacity. (2) Methods: BV2 microglia were treated with single interferon gamma (IFN-γ) stimulation, LPS/IFN-γ co-stimulation, and priming with IFN-γ followed by stimulation with LPS for 24 h. The responses of BV2 microglia were then assessed using the H2DCFDA test for iROS, the Griess assay for NO, immunophenotyping for CD40/CD11b/MHC II, and migration using a transwell apparatus. (3) Results: Single stimulation with IFN-γ induced NO but not ROS in BV2 microglia. Co-stimulation with LPS200IFN-γ2.5 induced a higher iROS production (a 9.2-fold increase) and CD40 expression (28031 ± 8810.2 MFI), compared to priming with primedIFN-γ50LPS100 (a 4.0-fold increase in ROS and 16764 ± 1210.8 MFI of CD40). Co-stimulation also induced cell migration. On the other hand, priming BV2 microglia (primedIFN-γ50LPS100) resulted in a higher NO production (64 ± 1.4 µM) compared to LPS200IFN-γ2.5 co-stimulation (44 ± 1.7 µM). Unexpectedly, priming inhibited BV2 migration. (4) Conclusions: Taken together, the findings from this project reveal the ability of co-stimulation and priming in stimulating microglia into an inflammatory phenotype, and the heterogeneity of microglia responses towards different stimulating approaches.